(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Optical coherence tomography angiography (OCTA) enables measuring characteristics of the retinal microvascular bed such as vascular plexus density and foveal avascular zone (FAZ) area. Purpose: To assess the OCTA changes in morphology and structural characteristics of the retinal microvascular bed in patients with exudative age-related macular degeneration (AMD). Materials and Methods: Forty seven patients with exudative AMD (51 eyes) and 13 healthy controls (22 eyes) were included in the study. OCTA was used to measure superficial plexus FAZ area (SPFA), deep plexus FAZ area (DPFA), vessel density and retinal thickness. Patients were divided into three groups based on the ratio of SPFA to DPFA: Group 1 (SPFA/DPFA < 0.6; 15 eyes), Group 2 (0.6 ≤ SPFA/DPFA < 0.8; 17 eyes), and Group 3 (SPFA/DPFA ≥ 0.8; 19 eyes). Results: Deep plexus FAZ area in all groups of patients was increased and superficial plexus FAZ area in Group 3 was significantly increased compared to controls. Patients in Group 1 exhibited mostly apparent signs of retinal edema and minimal alterations in the retinal microvascular bed. Patients in Group 2 had greater retinal thickness, but moderately lower plexus vessel density compared to controls. Patients in Group 3 had substantially lower superficial plexus vessel density and insubstantially altered retinal thickness compared to controls. Conclusion: OCTA enables assessing the changes in morphology and structure of the retinal microvascular bed, measuring FAZ area and vessel density in patients with exudative AMD.